Prevalence of Depression and Its Relationship to Care Engagement among Men Living with HIV - Mwanga, Martha Oshosen (Department of Psychology, 2023)
Background: The study was focused on the prevalence of depression among men living with HIV, who are in HIV care, and assessed the relationship between depression and care engagement. Several factors have been associated with care engagement among people living with HIV, including depression, but also lack disclosure due to stigmatization, poor social support, high pill burden, poor knowledge of ART, as well as young or old age. However, little is known about how these risk factors play out in men, as most of literature have been directed on women. Objectives: To understand the prevalence of depression in men living with HIV, attending Mawenzi Care and Treatment Clinic, and the effect of depression on care engagement. Method: A cross-sectional survey was conducted in the Mawenzi CTClinic, in Moshi, Kilimanjaro, Tanzania. Adult men living with HIV, 18 years and above, were invited to participate. A composite, continuous scale was developed to measure care engagement. At the clinic participants were asked about their medication adherence, their clinic cards were also checked for their viral load. Self-reported medication adherence and viral load were combined to form the outcome variable or as an indicator of patient care engagement. A total of 203 participants were enrolled in the study, with a mean age of 48 years. Results: The prevalence of depression among men living with HIV was 47.8 %: 35.0 % had mild symptoms, 8.9% moderate symptoms, and 3.9% severe symptoms. There was an indirect relationship between predictors: stigma was associated with depression and depression was associated with care engagement. Conclusion: HIV-related stigma and depression should not be underestimated because of their association with each other. Symptoms of depression need to be treated early, to reduce their effects on care engagement and hence disease progression.